Prioritizing chapter importance for intensive mathematics using fuzzy analytical hierarchy process / Nik Muhammad Farhan Hakim Nik Badrul Alam, Nazihah Ismail and Anisah Dasman - Nik Badrul Alam, Nik Muhammad Farhan Hakim; Ismail, Nazihah; Dasman, Anisah (Universiti Teknologi MARA Cawangan Pahang, 2021)
MAT037 is an intensive Mathematics course for pre-diploma students (Pre-Commerce) at Universiti Teknologi MARA. It is crucial for the lecturers to have a proper planning on teaching the course. This course includes six chapters, which are arithmetic and algebra (C1), equation and function (C2), index and logarithm (C3), sequence (C4), introduction to applications of mathematics in business (C5), and introduction to statistics (C6). The objective of this research is to rank the MAT037 chapters based on their importance. The fuzzy analytical hierarchy process (AHP) was used to rank the chapters. The use of fuzzy AHP which to produce the ranking helps the decision makers to make comparison of which chapter is more important than the other and the vagueness of the judgements was handled by the fuzzy basis which cannot be done by the classical AHP. The triangular fuzzy numbers were used to fuzzify the crisp values, and the centre of area defuzzification method was used at the end of the steps. The results showed that C1 is the most important topic meanwhile C4 is the least important among the chapters.